Seasonal levels of some haematobiochemical parameters in dairy cows - Ozdemir, H; Sezer, K; Kilic, S (Indian Veterinary Journal, 2005)
Purebred dairy cow breeding is very common in Turkey and has great impact on the country economy. Increased energy and vitamin demands of these animals or their inadequate and unbalanced nutrition may be associated with many problems (Kocak, 2002). The blood components of these animals may present some fluctuations due to a number of factors including nutrition, environment, age, breed, sex, gestation, parturition and lactation status (Jain, 1993). The purpose of the present study was to analyze the seasonal concentrations of some haematological and biochemical parameters in the dairy COWS.